1993
DOI: 10.1093/oxfordjournals.aje.a116770
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Community-Acquired Pneumonia in the Population of Four Municipalities in Eastern Finland

Abstract: Between September 1, 1981, and August 31, 1982, all patients with suspected or confirmed pneumonia among the 46,979 inhabitants of four municipalities in the province of Kuopio, Finland, were reported to a pneumonia register by their attending physicians. In addition, two study pathologists reported all cases of pneumonia found at autopsy, and two permanent registers were checked for retrospective identification of patients. Chest radiographs were obtained from 97% of all patients. The final diagnosis was base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
309
7
16

Year Published

1996
1996
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 490 publications
(365 citation statements)
references
References 0 publications
29
309
7
16
Order By: Relevance
“…This period of life is characterized by the occurrence of chronic and debilitating conditions, which tend to be more frequent in males and have been found to be a major risk factor for community-acquired pneumonia [7]. Similar trends in the incidence rates stratified by age and sex were found in the Finnish population-based study [3]. The incidence rate of pneumonia also varied annually and in the authors' Mediterranean climate, winter (2.21) and autumn (1.59) had the highest rates.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…This period of life is characterized by the occurrence of chronic and debilitating conditions, which tend to be more frequent in males and have been found to be a major risk factor for community-acquired pneumonia [7]. Similar trends in the incidence rates stratified by age and sex were found in the Finnish population-based study [3]. The incidence rate of pneumonia also varied annually and in the authors' Mediterranean climate, winter (2.21) and autumn (1.59) had the highest rates.…”
Section: Discussionsupporting
confidence: 56%
“…This figure, however, was obtained from the US National Health Survey's population sample interview, all ages were included, and no roentgenographic confirmation of pneumonia was required. In European population-based studies, a lower incidence of community-acquired pneumonia has been reported, such as 5 per 1,000 persons between 15±79 yrs of age in England [12], and 9 per 1,000 inhabitants >14 yrs of age in Finland [3]. In Spain, SANTOS DE UNAMUNO et al [13] reported an incidence rate of 1.8 per 1,000 inhabitants >14 yrs of age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations